Oxygen-selective adsorption in RPM3-Zn metal organic framework. (29th June 2017) - Wang, Cheng-Yu; Wang, Linxi; Belnick, Andrew; Wang, Hao; Li, Jing; Lueking, Angela D.
Highlights: Oxygen selectivity in the RPM3-Zn applicable to air separation is observed. Thermodynamic oxygen selectivity is attributed to metal sites. Kinetic selectivity is attributed to sharp temperature-dependent gate-opening process. Abstract: Development of an oxygen selective adsorbent is anticipated to reduce the material and energy requirements for adsorptive separations of air by a factor of four, due to the relative concentrations of N2 and O2 in air, thereby decreasing the parasitic energy losses, carbon dioxide emissions, and cost of oxygen purification via pressure-swing adsorption. Here, we report that RPM3-Zn (a.k.a. Zn2 (bpdc)2 (bpee); bpdc = 4, 4′-biphenyldicarboxylate; bpee = 1, 2-bipyridylethene) is oxygen selective over nitrogen at temperatures from 77 K to 273 K, although the oxygen capacity of the sorbent decreased markedly at increasing temperatures. Due to an oxygen diffusivity that is ∼1000-fold greater than nitrogen, the effective oxygen selectivity increases to near infinity at low temperature at equal contact times due to N2 mass transfer limitations for gate-opening. The kinetic limitation for N2 to open the structure has a sharp temperature dependence, suggesting this effective kinetic selectivity may be "tuned in" for other flexible metal-organic-frameworks. Although the low temperature oxygen selectivity is not practical to displace cryogenic distillation, the results suggest a new mechanism for tailoring materials for kinetic selectivity, namely, capitalizing upon the delayed opening process for a particular gas relative to another.